Well-Being Lessons for Improving Charities’ Online Recruitment - Buenadicha-Mateos, Maria; Sánchez Hernández, Maria Isabel; González-López, Oscar R.; Tato-Jiménez, Juan Luis (Frontiers in Psychology, 2019)
In an increasingly competitive context, attracting and retaining the best employees is a real preoccupation and a big challenge for organizations. Online recruitment is a growing trend, and corporate websites are an important instrument for talent attraction, but academic research on this topic is still scarce, especially in the voluntary sector. To shed light on the topic, this study examines and compares the 100 best companies to work for, published by Fortune, and the 100 largest charities, reported by Forbes. The comparative study focuses the attention and quantifies the web section devoted to careers, concretely information related to goods practices affecting the workers wellbeing. The results indicated, as essential in the online recruitment process of charities, to understand the relevance of their web content because that affects the intentions of potential applicants. The work concludes that benchmarking efforts can be helpful for increasing the charities' attractiveness in the labor market in the near future.